2011
DOI: 10.1038/jcbfm.2011.123
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Parametric Mapping Demonstrates Asymmetric Uptake with Tc-99m ECD and Tc-99m HMPAO SPECT in Normal Brain

Abstract: Tc-99m ethyl cysteinate diethylester (ECD) and Tc-99m hexamethyl propylene amine oxime (HMPAO) are commonly used for single-photon emission computed tomography (SPECT) studies of a variety of neurologic disorders. Although these tracers have been very helpful in diagnosing and guiding treatment of neurologic disease, data describing the distribution and laterality of these tracers in normal resting brain are limited. Advances in quantitative functional imaging have demonstrated the value of using resting studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…Taking into account that perfusion is 4 to 5-fold higher in gray matter than in white matter, this finding appears to conform with extensive asymmetry of gray matter density in healthy subjects, higher in the right hemisphere in the frontal and temporal cortex (Good et al, 2001). However, in a very recent study using a statistical parametric mapping approach very similar to the one used in the present study, Brinkmann and co-workers found larger HMPAO (and ECD) uptake in the left hemisphere compared with the right in neurologically normal volunteers (Brinkmann et al, 2011). The asymmetry affected widespread cortical areas, in good agreement with the present findings in mice (Fig.…”
Section: Lateral Asymmetrysupporting
confidence: 63%
“…Taking into account that perfusion is 4 to 5-fold higher in gray matter than in white matter, this finding appears to conform with extensive asymmetry of gray matter density in healthy subjects, higher in the right hemisphere in the frontal and temporal cortex (Good et al, 2001). However, in a very recent study using a statistical parametric mapping approach very similar to the one used in the present study, Brinkmann and co-workers found larger HMPAO (and ECD) uptake in the left hemisphere compared with the right in neurologically normal volunteers (Brinkmann et al, 2011). The asymmetry affected widespread cortical areas, in good agreement with the present findings in mice (Fig.…”
Section: Lateral Asymmetrysupporting
confidence: 63%
“…In a recent study, Brinkmann et al [1] reported left > right perfusion asymmetry in widespread areas of the cerebral hemispheres in SPECT images of neurologically normal volunteers, based on examination of the images using semi-automated ROI analysis and statistical parametric mapping (SPM). In view of this previous report, our present results showing right > left rCBF asymmetry in patients with oral cenesthopathy could have important implications.…”
Section: Discussionmentioning
confidence: 99%
“…There was also less left-right asymmetry in our GRN mutation carriers, which we interpret as an indication of more marked metabolic abnormalities in the right hemisphere in light of reports of increased right-sided regional or global tracer uptake in normal subjects on FDG-PET and HMPAO SPECT. 14,23 These global abnormalities were present in both asymptomatic and CSND carriers. Concurrent localization with ROI and SPM analyses highlighted right medial and ventral regions in the frontal lobe.…”
Section: 56mentioning
confidence: 96%